Peran Organisasi Rumah Internet Bagi Masyarakat Melalui Pembangunan Rumah Baca Di De-sa Kurandak - Ratih Ramadhan; Muhammad Dalimunte (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
The purpose of writing this research is to find out the role of Rumah Internet for Kurandak Villagers through the construction of a Rumah Baca and what obstacles are faced when carrying out the planned programs. The research method used descriptive method with a qualitative approach through data collection techniques by doing observation, interviews, documentation, and library research. The subjects of this study are the organizers of Rumah Internet and Rumah Baca. The results of this study indicated that the organization of Rumah Internet its desire to advance the village Though its programs that have been planned as a strategy to succeed in the wishes of the founders of Rumah Internet. There are four main goals of Rumah Internet namely; success the village through of technology, literacy, agriculture and the creative economy. The obtacles are insufficient funds, the location is too remote, and the children prefer to play than study. Keywords: Organization, Rumah Internet, Rumah Baca, Hinterland, Development